(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the hokku, a genre of Japanese poetry, were subjected to analysis based on translations by Rauf Parfi and Khurshid Davron. Through comparative-typological, cultural-historical methods, hokku’s genre features, composition, scope of topics are covered. The issue of literary influence is revealed in the introduction to the Khurshid Davron creative laboratory. Based on poems by the Japanese poets Basyo and Hattori Ransetsu, aspects specific to the hokku, in which the interactions of nature and the human mood are shown through analysis.